Genetic variability at promoters of IL-18 (pro-) and IL-10 (anti-) inflammatory gene affects susceptibility and their circulating serum levels: An explorative study of prostate cancer patients in North Indian populations. Issue 1 (July 2015) - Dwivedi, Shailendra; Goel, Apul; Khattri, Sanjay; Mandhani, Anil; Sharma, Praveen; Misra, Sanjeev; Pant, Kamlesh Kumar
Highlights IL-18 and IL-10 promoter genetic variants affect prostate carcinoma susceptibility. IL-18 and IL-10 promoter genetic variants affect circulatory protein levels. IL-18 protein levels showed a trend of GG > GC > CC at −137 of IL-18 in PCa. IL-10 protein levels showed a trend of CC > CT > TT at −819 of IL-10 in all groups.